2003
DOI: 10.1590/s0102-35862003000500004
|View full text |Cite
|
Sign up to set email alerts
|

Tabagismo em amostra de adolescentes escolares de Salvador-Bahia

Abstract: Introdução: O hábito de fumar em geral se inicia na adolescência. No Brasil, as estimativas da freqüência deste hábito entre adolescentes variam de 1% até 35%.Objetivo: Estimar a prevalência do tabagismo entre os adolescentes da oitava série do ensino fundamental à terceira série do curso médio, em escolas de Salvador -Bahia, Brasil. Método:Feito um estudo do tipo corte transversal de caráter exploratório. Foram aplicados 3.500 questionários a alunos matriculados entre a 8ª série do ensino fundamental e a 3ª s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
2
0
7
Order By: Relevance
“…3 The In Brazil, there is not a systematized health risk behavior surveillance program for the adolescent population. Studies concentrate results on isolated behaviors, such as alcohol and tobacco use, 11,13,18,21 illicit drug use, 8,15,19 dietary habits 1,6,16,20 and physical activity practice. 9,14,16,17 Instruments to gather information that have been standardized to the Portuguese language are not easily identifi ed.…”
Section: Introductionmentioning
confidence: 99%
“…3 The In Brazil, there is not a systematized health risk behavior surveillance program for the adolescent population. Studies concentrate results on isolated behaviors, such as alcohol and tobacco use, 11,13,18,21 illicit drug use, 8,15,19 dietary habits 1,6,16,20 and physical activity practice. 9,14,16,17 Instruments to gather information that have been standardized to the Portuguese language are not easily identifi ed.…”
Section: Introductionmentioning
confidence: 99%
“…Carlini et al (2002) showed that in Brazil, 2001, the prevalence of tobacco users was estimated as 9.0% of the population, equivalent to 4,214,000 people. Similarly in 1998, young students from 13 to 20 years old in Salvador, Brazil, have smoking prevalence of 9.5% (Machado Neto and Cruz 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Há que se considerar que, dentre os participantes que afirmaram ter consumido álcool e tabaco no último mês, 33,4% e 42% respectivamente tinham feito o consumo regular dessas substâncias. Nessa direção, estudo realizado com jovens de uma capital do Nordeste brasileiro demonstrou que, dentre os participantes que relataram ter experimentado o uso de cigarro, 20,4% desenvolveram o hábito de fumar e 28,4% iniciaram o uso entre 11 a 13 anos (Machado Neto & Cruz, 2003).…”
Section: Discussionunclassified